Modeling and simulation of drop behaviour of multipack products - Kambhampati Venugopal. (2008)
In this project, finite element modeling procedure is developed to conduct drop impact simulation on four packaging materials using Ansys (LS Dyna). The corresponding cushioning curves for the materials are obtained in which the package is then designed.